The value of a statistical injury: new evidence from the Swiss labor market - Andreas Kuhn; Oliver Ruf (Institute for the Study of Labor (IZA), 2009)
We study the monetary compensation for non-fatal accident risk in Switzerland using the number of accidents within cells defined over industry x skill-level of the job and capitalizing on the partial panel structure of our data which allows us to empirically isolate the wage component specific to the employer. Our results show that using accident risk at a lower level of aggregation, using narrower samples of workers, and using the wage component that is specific to the firm all yield higher estimates of risk compensation. Our preferred estimate gives an estimate of about 36,000 Swiss francs per prevented injury per year.
Keywords: J17; J28; J31; 330; Compensating wage differentials; value of a statistical injury; risk measurement; Gesundheit; Messung; Wert des Lebens; Lohnstruktur; Arbeitsproduktivität; Schweiz